Examining the Development of Social Skills in First-Grade Elementary School Children - Ismail, Nyak Mutia; Putri, Zaiyana; Moriyanti, Moriyanti; Rahma, Endah Anisa (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study explores how social skills are performed among first-grade elementary school children, focusing on key competencies such as communication, cooperation, and conflict resolution. Through qualitative observations and analyses, the study examines how individual differences influence children's social interactions and ability to adapt to structured educational environments. The data were collected using interview guides and documentation, which were later analyzed using thematic analysis. The findings reveal that there are three significant notes. First, regarding the communication pattern, the children are more intimate and relaxed when talking to peers and feel more serious when talking to teachers. Second, their ability to cooperate is shown in taking turns. Third, in resolving the anger conflict, they mostly stay silent, believing that it will disappear, and they find their teachers to help end the conflict. It is later concluded that first-grade children adapt their social skills based on context, showing different communication styles, cooperation, and conflict-resolution strategies with peers and adults. This implies that school teachers must pay attention to the student's ability to develop their social skills.